A Critical Examination of Pascal Boyer’s Religion Explained The Evolutionary Origins of Religious Thought - Dubuisson, Daniel (Method & theory in the study of religion, 2020)
Behind its theoretical and scientific ambition, Pascal Boyer’s work mobilizes several ideas and notions (starting with that of “religion”) that belong to the old Western cultural tradition. It is precisely this ideological substratum and its indispensable cognitive “crutches” that this article seeks to identify.